The Influence of Consistent Discipline Development on Student Character Development at SDN 02 Ciganjur - Jody Purwanto; Siskha Putri Sayekti; Muhammad Latif; Lisa Andini; Syifa’ Hannan (Konsultan Jurnal Ilmiah Indonesia, 2025)
This research explores strategies for fostering student discipline at State Elementary School 02 Ciganjur using a qualitative approach. Data was collected through observation, in-depth interviews, and document analysis. The research results show that discipline development at SDN 02 Ciganjur uses a combination of preventive and corrective approaches. The preventive approach involves instilling character values, consistent application of rules, and providing rewards, while the corrective approach includes educational sanctions and individual counseling. Success factors include principal leadership, parent involvement, and a supportive school environment. Positive relationships between teachers and students also greatly influence disciplinary behavior. This research concludes that a holistic and collaborative approach is important for effective discipline development in elementary schools.